Key factor intrapreneurship : the development of a systems model to facilitate the perpetuation of entrepreneurship in the larger South African organisation - Goosen, Christiaan Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2002.